Role of the Media in Health-Related Awareness Campaigns on Perception of COVID-19: A Pre-post Study in the General Population of Pakistan - Rehman, Atta Ur; Zakar, Rubeena; Zakar, Muhammad Zakria; Hani, Ume; Wrona, Kamil J.; Fischer, Florian (Frontiers in Public Health, 2021)
Medical preparedness and community education are the most valuable preventive tools for combatting the COVID-19 pandemic. This study aims to assess the role of media public health awareness campaigns on the knowledge of the general population about COVID-19 in Rawalpindi, Pakistan. A quantitative study using a pre-post design among 384 respondents was conducted. A structured questionnaire was administered to the participants twice: The first response (t1) from participants was filled in during the first week in February 2020 before any confirmed cases were reported in the country, and the second response (t2) was completed one month after the first case detection in Pakistan (March 2020). Media health awareness campaigns were launched just after the detection of the first case in Pakistan. Exposure to the media and knowledge relating to COVID-19 increased over time. Whereas only a quarter of respondents judged the isolation of suspected cases in quarantine to be important to prevent the spread of infection in society at t1, more than half did so at t2. Socio-demographic characteristics were not significantly associated with knowledge (gains). However, more frequent use of electronic media is associated with greater knowledge gains from t1 to t2. The findings of this study provide evidence that awareness and knowledge related to COVID-19 symptoms and preventive measures increased significantly over time. The increased frequency of following the media indicates that health awareness campaigns are important for enhancing the knowledge of the general public regarding COVID-19.